COMMUNITY ECONOMIC EMPOWERMENT THROUGH VILLAGE ORGANIC VEGETABLE VILLAGE PROGRAM IN NGEMPLAK SUTAN VILLAGE, MOJOSONGO VILLAGE, JEBRES DISTRICT, SURAKARTA CITY - Niko Satya Gunawan; Nina Widowati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Community empowerment through Kampung Sayur Organik Ngemplak Village is one of the solutions carried out by the Surakarta Regional Government in an effort to overcome the declining productive agricultural land and poverty in Surakarta City. However, in the implementation of commitment from the community and the percentage of achievement of each program activities are still not maximal. This study aims to further analyze how the economic empowerment of the community through organic vegetable programs in Ngemplak Village and the factors that influence it. The method used is descriptive qualitative research method. The data was collected through interview techniques for primary data, with 6 sources determined using snowball sampling techniques. Then documentation techniques for secondary data. The data analysis process uses miles and huberman models and is examined the quality of data obtained using triangulation techniques. The results showed that the implementation of empowerment through Kampung Sayur Organik in Ngemplak Village is still not maximal because of inappropriate access, critical awareness of the community that is still lacking, and participation that is still lacking. Factors that influence the implementation of empowerment are supportive environmental conditions, uneven human resources in obtaining an education, and characteristics and implementing agents that are not maximal in providing training and education. The advice that researchers can give is that there needs to be socialization and increased community participation.